Impact Properties of Aluminum Foam – Nanosilica Filled Basalt Fiber Reinforced Polymer Sandwich Composites - Emi Nor Ain Mohammad, Nurul; Jumahat, Aidah; Fashan Ghazali, Mohamad (International Journal of Engineering and Technology, 2018)
This paper investigates the effect of nanosilica on impact and energy absorption properties of sandwich foam-fibre composites. The materials used in this study are closed-cell aluminum (Al) foam (as the core material) that is sandwiched in between nanomodified basalt fiber reinforced polymer (as the face-sheets). The face sheets were made of Basalt Fibre, nanosilica and epoxy polymer matrix. The sandwich composite structures are known to have the capability of resisting impact loads and good in absorbing energy. The objective of this paper is to determine the influence of closed-cell aluminum foam core and nanosilica filler on impact properties and fracture behavior of basalt fibre reinforced polymer (BFRP) sandwich composites when compared to the conventional glass fibre reinforced polymer (GFRP) sandwich composites. The drop impact tests were carried out to determine the energy absorbed, peak load and the force-deflection behaviour of the sandwich composite structure material. The results showed that the nanomodified BFRP-Al foam core sandwich panel exhibited promising energy absorption properties, corresponding to the highest specific energy absorption value observed. Also, the result indicates that the Aluminium Foam BFRP sandwich composite exhibited higher energy absorption when compared to the Aluminium foam GFRP sandwich composite.Â Â